Functional particles with radically polymerizable groups introduced via urethane bonds

The radiation polymerizable group is introduced into the surface of the inorganic filler through urea bonds, which solves the problem of residual polyhydroxy groups on the surface of the filler in the prior art, and achieves high mechanical strength and weather resistance of the material.

JP2025059573APending Publication Date: 2025-04-10SHOFU INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023169733
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

In the prior art, when a silane coupling agent is used to introduce radiation polymerizable groups into the surface of the inorganic filler, it is limited by the dehydration and solidification reaction at high temperature, resulting in polyhydroxy groups remaining on the surface of the filler, resulting in insufficient mechanical strength and weather resistance of the material.

Method used

By introducing the radiation polymerizable group into the polyhydroxy groups on the surface of the inorganic filler using urea bonds, high-density functional particles are formed, and the formation of the fragile xerogel layer is avoided.

Benefits of technology

The introduction of high-density radiation polymerizable groups on the surface of inorganic fillers has been achieved, which significantly improves the mechanical strength and weather resistance of the material, and is suitable for medical, dental and industrial uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059573000001
    Figure 2025059573000001
  • Figure 2025059573000002
    Figure 2025059573000002
  • Figure 2025059573000003
    Figure 2025059573000003
Patent Text Reader

Abstract

To solve the problems that, in addition to radically polymerizable monomers, medical and dental hardening compositions contain, in order to improve mechanical strength, inorganic fillers surface-treated with silane coupling agents having a radically polymerizable group (including the conventionally widely used γ-methacryloxypropyltrimethoxysilane (hereinafter referred to as KBM-503)) for improving wettability and mechanical strength, however, since these silane coupling agents have a carbon skeleton, the drying temperature during the dehydration-condensation after dealcoholizing limited, resulting in incomplete dehydration-condensation of the generated silanol groups and, as a result, having a brittle xerogel layer causes the expected mechanical strength and durability to not be obtained.SOLUTION: Provided is a functional fine particle characterized in that at least 90% of the silanol groups on the surface of an inorganic filler have radical polymerizable groups introduced therein via urethane bonds.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to functional fine particles characterized in that radically polymerizable groups are introduced via urethane bonds to silanol groups on the surface of an inorganic filler. [Background technology]

[0002] In the medical and dental fields, metal prostheses and synthetic resin moldings are used to repair bone and tooth defects. Adhesives containing adhesive polymerizable monomers are often used to bond them to biological hard tissues. In the field of dental conservation, curable compositions called composite resins and resin-reinforced glass ionomer cements are used in clinical practice on a daily basis. In composite resins, uncured (before radical polymerization) paste is filled into the defect site of a tooth or the like, and then external energy such as light irradiation is applied to obtain a radically polymerized cured product. Generally, these adhesives and composite resins use (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bond is cleaved to become a single bond, forming a polymer and hardening. In addition to vinyl monomers, inorganic fillers are added to this composite resin for the purpose of improving mechanical strength. In general, these inorganic fillers are surface-treated with a silane coupling agent having a polymerizable group to improve wettability and mechanical strength.

[0003] In the dental field, γ-methacryloxypropyltrimethoxysilane (hereinafter referred to as KBM-503) has been widely used as a silane coupling agent. When particles surface-treated with this compound are used, the inorganic filler surface is indeed hydrophobized by the surface treatment, and some improvement in mechanical strength is observed. However, since these silane coupling agents have a radical polymerizable group in the carbon skeleton, the drying temperature after surface treatment is limited to about 150°C. Here, the alkoxy group of the silane coupling agent is hydrolyzed, and the silanol group generated thereafter undergoes dehydration condensation to form a polysiloxane bond. A high drying temperature is effective in promoting this dehydration condensation. If sufficient dehydration condensation is not performed, the generated silanol group remains in a xerogel state, and sufficient mechanical strength cannot be obtained. To explain in more detail, the silanol group on the filler surface and the silanol group generated by dealcoholization of the silane coupling agent are chemically strongly bonded by dehydration condensation. This dehydration condensation generally proceeds spontaneously, but when the reaction points are far apart, molecular vibration due to heating is required. It goes without saying that higher heating is required for dehydration condensation between reaction points that are far apart. However, as mentioned above, silane coupling agents having radical polymerizable groups undergo polymerization at high temperatures exceeding 150°C and lose their function as silane coupling agents. Therefore, the upper limit of the heating temperature is limited, and as a result, a fragile xerogel layer remains, resulting in a decrease in mechanical strength. This problem was unavoidable as long as a silane coupling agent that introduces radical polymerizable groups into inorganic fillers by hydrolysis and condensation of alkoxy groups is used. In order to alleviate the fragility, a method using a silane coupling agent with a long alkyl chain (Patent Documents 1 and 2), a method using a silane coupling agent having a fluoroalkylene group (Patent Document 3), and a method using a silane coupling agent having many polymerizable groups (Patent Document 4) have been proposed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2-134307 [Patent Document 2] Japanese Patent Publication No. 3-70778 [Patent Document 3] Patent Publication No. 2007-238567 [Patent Document 4] Patent Publication No. 2010-229054 Summary of the Invention [Problem to be solved by the invention]

[0005] Silane coupling agents that introduce radical polymerizable groups into inorganic fillers by hydrolysis and condensation of alkoxy groups undergo dehydration and condensation of the silanol groups generated after hydrolysis to form polysiloxane bonds. A high drying temperature is effective in promoting this dehydration and condensation. If the dehydration and condensation is not sufficient, the generated silanol groups remain in a xerogel state, and sufficient mechanical strength cannot be obtained. In addition, the xerogel exhibits hydrophilicity. However, since the silane coupling agent has a radical polymerizable group of the carbon skeleton, the drying temperature after surface treatment is limited to about 150°C or less. Therefore, dehydration and condensation are not sufficiently performed, and the silanol groups remain, resulting in hydrophilicity. Therefore, in order to increase hydrophobicity, a method of using a silane coupling agent with a long alkyl chain (Patent Documents 1 and 2), a method of using a silane coupling agent with a fluoroalkylene group (Patent Document 3), and a method of using a silane coupling agent with many polymerizable groups (Patent Document 4) have been proposed. However, when the methods described in Patent Documents 1 to 3 are applied to dental materials, there is still room for improvement in mechanical strength. In addition, when the method described in Patent Document 4 is applied to dental materials, the durability of the materials is insufficient. Thus, the compatibility of durability and mechanical strength of materials using silane coupling agents in the conventional technology is insufficient, and there is room for further improvement. However, as mentioned above, it must be said that it is scientifically difficult to achieve with the conventional technology. [Means for solving the problem]

[0006] As a result of intensive research by the inventors, it was found that by including functional fine particles characterized in that radical polymerizable groups are introduced via urethane bonds to 90% or more of the silanol groups on the surface of an inorganic filler, high mechanical strength and durability were obtained in a hardenable composition, which can improve the mechanical strength and durability not only when used in medical and dental hardenable compositions but also when used in general industrial materials such as electronic industrial parts. Effect of the Invention

[0007] The functional microparticles, which have radically polymerizable groups introduced at a high density via urethane bonds to the hydroxyl groups on the surface of the inorganic filler contained in the medical and dental hardening composition of the present invention, do not have any of the brittle xerogel layer that occurs when surface treatment is performed using a conventional silane coupling agent, and it is possible to introduce radically polymerizable groups to the surface of the inorganic filler through strong covalent bonds. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Functional fine particles having radical polymerizable groups introduced via urethane bonds to 90% or more of the silanol groups on the inorganic filler surface can be synthesized by the following synthesis method. In this synthesis method, functional fine particles obtained by reacting hydroxyl groups on the inorganic filler surface with an organic compound having a radical polymerizable group at one end and generating an isocyanate group when heated are free of a fragile xerogel layer, and radical polymerizable groups can be introduced to the inorganic filler surface via strong covalent bonds.

[0009] [ka]

[0010] The above is a schematic diagram of the surface modification of inorganic fillers using a silane coupling agent, which is a conventional technology. That is, the silane coupling agent is partially or completely dealcoholized and converted to a silanol group, and then dehydration condensation with the silanol group on the surface of the inorganic filler such as glass is performed to perform surface modification. Due to the presence of reactive groups such as radical polymerizable carbon skeletons, dehydration condensation cannot be performed completely at high temperatures exceeding 150 ° C, and free silanol groups are also present. In contrast, in the functional fine particles contained in the present invention, as shown below, the silanol group on the surface of the inorganic filler such as glass reacts with the isocyanate group, and the surface is reliably modified by urethane bonds. Therefore, there is no fragile xerogel layer as in the case of using the silane coupling agent of the conventional technology, and it is possible to introduce radical polymerizable groups into the surface of the inorganic filler through strong covalent bonds.

[0011] [ka]

[0012] The chemical structural formula of an organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating is shown below.

[0013] [ka]

[0014] [ka]

[0015] For functional microparticles characterized in that radically polymerizable groups are introduced via urethane bonds to 90% or more of the silanol groups on the surface of the inorganic filler, an organic compound can be used that has a radically polymerizable group at one end and generates an isocyanate group when heated.

[0016] The organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating is preferably selected from the following:

[0017] [ka]

[0018] [ka]

[0019] [ka]

[0020] The organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating, which can be used in the production of the functional fine particles of the present invention, is: (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate, 2-(3,5-dimethyl-1H-pyrazole-1-carboxamido)ethyl methacrylate, and (2,4-dioxo-1,3-diazetidine-1,3-diyl)bis(ethane-2,1-diyl)bis(2-methylacrylate) are most preferably used. These can be used alone or in combination of two or more kinds.

[0021] The medical and dental hardening composition of the present invention is preferably composed as follows. That is, the inorganic filler, which is the precursor of the functional fine particles contained in the present invention, includes silicon dioxide, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, etc. In particular, fluoroaluminosilicate barium glass, fluoroaluminosilicate strontium glass, fluoroaluminosilicate glass, etc., which are used in dental glass ionomer cement, resin-reinforced glass ionomer cement, resin cement, etc., can also be preferably used. The fluoroaluminosilicate glass referred to here has a basic skeleton of silicon oxide and aluminum oxide, and contains an alkali metal for introducing non-bridging oxygen. It further contains alkaline earth metals including strontium and fluorine as modifying and coordinating ions. It is also a composition in which a lanthanoid series element is incorporated into the skeleton to impart further X-ray opacity. The lanthanoid series element also participates in the composition as a modifying and coordinating ion depending on the composition range. These elements can be used alone or in combination of two or more kinds. Furthermore, the average particle size of the inorganic filler is preferably 0.001 to 100 μm, more preferably 0.001 to 10 μm. Furthermore, the shape of the inorganic filler may be either spherical or irregular.

[0022] As the chemical polymerization initiator (polymerization initiator), an organic peroxide is preferably used. The organic peroxide used in the above-mentioned chemical polymerization initiator is not particularly limited, and known organic peroxides can be used. Representative organic peroxides include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates.

[0023] Specific examples of the ketone peroxide used as the chemical polymerization initiator include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.

[0024] Specific examples of hydroperoxides used as chemical polymerization initiators include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.

[0025] Specific examples of diacyl peroxides used as chemical polymerization initiators include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.

[0026] Specific examples of dialkyl peroxides used as chemical polymerization initiators include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.

[0027] Specific examples of peroxyketals used as chemical polymerization initiators include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, and 4,4-bis(t-butylperoxy)valeric acid-n-butyl ester.

[0028] Specific examples of peroxy esters used as chemical polymerization initiators include α-cumyl peroxy neodecanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxy isophthalate, di-t-butyl peroxy hexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxy acetate, t-butyl peroxy benzoate, and t-butyl peroxy maleric acid.

[0029] Specific examples of peroxydicarbonates used as chemical polymerization initiators include di-3-methoxyperoxydicarbonate, di-2-ethylhexylperoxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, diisopropylperoxydicarbonate, di-n-propylperoxydicarbonate, di-2-ethoxyethylperoxydicarbonate, and diallylperoxydicarbonate.

[0030] When the chemical polymerization initiator is an aqueous redox polymerization initiator system, examples of a system that can be suitably used include ammonium persulfate / ascorbic acid, potassium persulfate / ascorbic acid, and the like.

[0031] Among the organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is particularly preferably used.

[0032] Specific examples of the polymerization accelerator include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, and thiol compounds.

[0033] The amines used as polymerization accelerators are divided into aliphatic amines and aromatic amines.Specific examples of aliphatic amines include n-butylamine, n-hexylamine, n-octylamine, diisopropylamine, dibutylamine, N-methyldiethanolamine, N-methylethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, tributylamine, etc.Among these, from the viewpoint of the curability and storage stability of the composition, tertiary aliphatic amines are preferred, and among them, N-methyldiethanolamine and triethanolamine are more preferably used.

[0034] Specific examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-di(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-dimethyl-m-toluidine. dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-N,N-dimethylaminobenzoic acid ethyl ester, 4-N,N-dimethylaminobenzoic acid methyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, 4-N,N-dimethylaminobenzoic acid-2-(methacryloyloxy)ethyl ester, 4-N,N-dimethylaminobenzophenone, 4-dimethylaminobenzoic acid butyl, and the like. Among these, from the viewpoint of imparting excellent curing properties to the composition, N,N-di(2-hydroxyethyl)-p-toluidine, 4-N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, and 4-N,N-dimethylaminobenzophenone can be mentioned.

[0035] Specific examples of sulfinic acids and salts thereof used as the polymerization accelerator include p-toluenesulfinic acid, sodium p-toluenesulfinate, potassium p-toluenesulfinate, lithium p-toluenesulfinate, calcium p-toluenesulfinate, benzenesulfinic acid, sodium benzenesulfinate, potassium benzenesulfinate, lithium benzenesulfinate, calcium benzenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinate, potassium 2,4,6-trimethylbenzenesulfinate, lithium 2,4,6-trimethylbenzenesulfinate, calcium 2,4,6-trimethylbenzenesulfinate, 2,4,6-triethylbenzenesulfinate, and the like. Examples of the sulfinic acid include benzenesulfinic acid, sodium 2,4,6-triethylbenzenesulfinate, potassium 2,4,6-triethylbenzenesulfinate, lithium 2,4,6-triethylbenzenesulfinate, calcium 2,4,6-triethylbenzenesulfinate, 2,4,6-triisopropylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinate, potassium 2,4,6-triisopropylbenzenesulfinate, lithium 2,4,6-triisopropylbenzenesulfinate, and calcium 2,4,6-triisopropylbenzenesulfinate. Of these, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2,4,6-triisopropylbenzenesulfinate are particularly preferred.

[0036] Specific examples of the borate compound used as the polymerization accelerator include borate compounds having one aryl group in one molecule, such as trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(3,5-bistrifluoromethyl)phenyl boron, trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl] boron, trialkyl(p-nitrophenyl) boron, trialkyl(m-nitrophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(m-butylphenyl) boron, and trialkyl(p-nitrophenyl) boron. Examples of suitable alkyl groups include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of trialkyl(p-butyloxyphenyl)boron, trialkyl(m-butyloxyphenyl)boron, trialkyl(p-octyloxyphenyl)boron, and trialkyl(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0037] Specific examples of borate compounds having two aryl groups in one molecule include dialkyldiphenylboron, dialkyldi(p-chlorophenyl)boron, dialkyldi(p-fluorophenyl)boron, dialkyldi(3,5-bistrifluoromethyl)phenylboron, dialkyldi[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, dialkyldi(p-nitrophenyl)boron, dialkyldi(m-nitrophenyl)boron, dialkyldi(p-butylphenyl)boron, dialkyldi(m-butylphenyl)boron, and dialkyldi(p-butyloxophenyl)boron. Examples of such an alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of dialkyldi(m-butyloxyphenyl)boron, dialkyldi(p-octyloxyphenyl)boron, and dialkyldi(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0038] Further, specific examples of borate compounds having three aryl groups in one molecule include monoalkyltriphenylboron, monoalkyltri(p-chlorophenyl)boron, monoalkyltri(p-fluorophenyl)boron, monoalkyltri(3,5-bistrifluoromethyl)phenylboron, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, monoalkyltri(p-nitrophenyl)boron, monoalkyltri(m-nitrophenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(m-butylphenyl)boron, monoalkyltri(p ...butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron Examples of the alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of alkyltri(p-butyloxyphenyl)boron, monoalkyltri(m-butyloxyphenyl)boron, monoalkyltri(p-octyloxyphenyl)boron, and monoalkyltri(m-octyloxyphenyl)boron (wherein the alkyl group is one selected from an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0039] Further specific examples of borate compounds having four aryl groups in one molecule include tetraphenylboron, tetrakis(p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis(3,5-bistrifluoromethyl)phenylboron, tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, tetrakis(p-nitrophenyl)boron, tetrakis(m-nitrophenyl)boron, tetrakis(p-butylphenyl)boron, tetrakis(m-butylphenyl)boron, tetrakis(p-butyloxyphenyl)boron, tetrakis(m-butyloxyphenyl)boron, tetrakis(p-octyloxyphenyl)boron, Examples of the salt include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of (m-octyloxyphenyl)triphenylboron, (p-fluorophenyl)triphenylboron, (3,5-bistrifluoromethyl)phenyltriphenylboron, (p-nitrophenyl)triphenylboron, (m-butyloxyphenyl)triphenylboron, (p-butyloxyphenyl)triphenylboron, (m-octyloxyphenyl)triphenylboron, and (p-octyloxyphenyl)triphenylboron.

[0040] Among these aryl borate compounds, it is more preferable to use a borate compound having 3 or 4 aryl groups in one molecule from the viewpoint of storage stability. In addition, these aryl borate compounds can be used alone or in combination of two or more kinds.

[0041] Specific examples of barbituric acid derivatives used as polymerization accelerators include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, Examples of barbituric acids include 1-cyclohexyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and thiobarbituric acids, as well as salts thereof (particularly preferred are those of alkali metals or alkaline earth metals). Examples of the salts of these barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate, and sodium 1-cyclohexyl-5-ethylbarbiturate.

[0042] Specific examples of particularly suitable barbituric acid derivatives include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and sodium salts of these barbituric acids.

[0043] Specific examples of triazine compounds used as the polymerization accelerator include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine. 2-(p-phenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl) -4,6-bis(trichloromethyl)-s-triazine, 2-styryl-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, chloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,Examples of the 6-bis(trichloromethyl)-s-triazine include 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine and 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.

[0044] Among the above-listed triazine compounds, 2,4,6-tris(trichloromethyl)-s-triazine is particularly preferred in terms of polymerization activity, and 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine are particularly preferred in terms of storage stability. The above-listed triazine compounds may be used alone or in combination of two or more.

[0045] Specific examples of copper compounds used as polymerization accelerators include copper acetylacetonate, copper acetate, copper oleate, copper chloride, and copper bromide.

[0046] Specific examples of tin compounds used as polymerization accelerators include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. Particularly preferred tin compounds are di-n-octyltin dilaurate and di-n-butyltin dilaurate. The vanadium compound used as the polymerization accelerator is preferably a tetravalent and / or pentavalent vanadium compound. Specific examples of the tetravalent and / or pentavalent vanadium compound include divanadium(IV) tetroxide, vanadium oxide acetylacetonate(IV), vanadyl oxalate(IV), vanadyl sulfate(IV), oxo-bis(1-phenyl-1,3-butanedionato)vanadium(IV), bis(maltolato)oxo-vanadium(IV), vanadium pentoxide(V), sodium metavanadate(V), and ammonium metavanadate(V).

[0047] Specific examples of halogen compounds used as polymerization accelerators include dilauryl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, benzyl trimethyl ammonium chloride, tetramethyl ammonium chloride, benzyl dimethyl cetyl ammonium chloride, and dilauryl dimethyl ammonium bromide.

[0048] Specific examples of aldehydes used as polymerization accelerators include terephthalaldehyde and benzaldehyde derivatives. Examples of benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methyloxybenzaldehyde, p-ethyloxybenzaldehyde, and pn-octyloxybenzaldehyde. Among these, pn-octyloxybenzaldehyde is preferably used from the viewpoint of curability.

[0049] Specific examples of the thiol compound used as the polymerization accelerator include 3-mercaptopropyltrimethoxysilane, 2-mercaptobenzoxazole, decanethiol, and thiobenzoic acid.

[0050] The inorganic filler used in the medical and dental hardenable composition of the present invention is not particularly limited in terms of its chemical composition, and examples thereof include silicon dioxide, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramics, and the like.

[0051] As the acid-reactive inorganic powder used in the medical and dental hardenable composition of the present invention, barium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, fluoroaluminosilicate glass, etc., which are used in dental glass ionomer cements, resin-reinforced glass ionomer cements, resin cements, etc., can be suitably used. The fluoroaluminosilicate glass referred to here has a basic skeleton of silicon oxide and aluminum oxide, and contains an alkali metal for introducing non-crosslinking oxygen. It further has alkaline earth metals including strontium and fluorine as modifying and coordinating ions. It is also a composition in which a lanthanoid series element is incorporated into the skeleton to impart further X-ray opacity. This lanthanoid series element also participates in the composition as a modifying and coordinating ion depending on the composition range. These can be used alone or in a mixture of two or more kinds.

[0052] The composition ratio of the acid-reactive inorganic powder and the functional fine particles in the dental composition of the present invention is not particularly limited, but is preferably within the range of 25 to 90% by weight. If it is 25% by weight or less, the mechanical (physical) strength of the cured product is low, which is not preferable. Moreover, if it is 90% by weight or more, the viscosity of the paste to be mixed is too high, which is not preferable because of poor clinical operability. Furthermore, the average particle size of the inorganic filler is preferably 0.001 to 100 μm, more preferably 0.001 to 10 μm. Furthermore, the shape of the acid-reactive inorganic powder and the functional fine particles may be either spherical or irregular.

[0053] The radical polymerizable monomer used in the medical and dental hardenable composition of the present invention may be any monomer used in the dental field without any limitation. Examples of such monomers include 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl dimethacrylate (UDMA) synthesized by the urethane reaction of 2,2,4-trimethylhexamethylene diisocyanate with 2-hydroxyethyl methacrylate (HEMA); radical polymerizable monomers synthesized by the urethane reaction of HEMA or HEA with 2,4-toluylene diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, or hexamethylene diisocyanate; urethane diacrylates obtained by the reaction of aliphatic and / or aromatic diisocyanates with glycerol (meth)acrylate or 3-methacrylol-2-hydroxypropyl ester; and urethane reactants of 1,3-bis(2-isocyanato, 2-propyl)benzene with a compound having a hydroxy group. More specifically, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 2,7,7,9,15-pentamethyl-4,13-18-trioxo-3,14,17-trioxa-5,12-diazaikos-19-enyl methacrylate, 2,8,10,10,15-pentamethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaikos-19-enyl methacrylate, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,1 2-Diazahexadecane-1,16-diylbis(2-methylacrylate), 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate, 2-((2-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate, 2-((4-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)bicyclo[4.1.0]heptane-3-yl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene) ) Bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 7,7,9-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicos-19-enyl methacrylate, 8,10,10-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicos -19-enyl methacrylate, 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methylacrylate), 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyldiacrylate, 4,13,18-trioxo-3,14,17-trioxa-5,12-diazaikos-19-enyl methacrylate, 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methyl acrylate), 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)-4,4-dimethylcyclohexyl)ethylcarbamoyloxy)ethyl methacrylate, 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)ethyl)-5,5-dimethylcyclohexylcarbamoyloxy)ethyl methacrylate, 2-(2-(((1-(methacryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methylacrylate), 2-(2-(((1-(methacryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diyldiacrylate, 2-(2-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methylacrylate), 3-(15-(2-(acryloyloxy)ethyl)-3,12,1 9-trioxo-2,13,18-trioxa-4,11-diazahenicos-20-enyl)pentane-1,5-diyl diacrylate, 3-(15-(2-(acryloyloxy)ethyl)-3,12,19-trioxo-2,13,18-trioxa-4,11-diazahenicos-20-enyl)pentane-1,5-diyl bis(2-methylacrylate), 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((2 -(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)ethyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methylacrylate), 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diyl diacrylate, 1-(cyclohexyloxy)-17-(cyclohexyloxymethyl)-5,14,19-trioxo-4,15,18-trioxa-6,13-diazahenicos-20-en-2-yl methacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diylbis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5, 12-Diazahexadecane-1,16-diyl diacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((3-((((2-(acryloyloxy)ethoxy)carbonyl)(methyl)amino)methyl)benzyl)(methyl)carbamoyloxy)ethyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl) diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)propyl methacrylate, 2-(3-(((1-(acryloyloxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl Methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bisoxomethylene)bis(oxy)bis(4,1-phenylene)bis(2-methylacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bisoxomethylene)bis(oxy)bis(4,1-phenylene)diacrylate, 4-(3-(((4-(acryloxy)phenoxy)carbonylamino)methyl)benzylcarbamoyloxy)phenyl Methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)bis(2-methylacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)diacrylate, 4-(3-(((4-(acryloyloxy)butoxy)carbonylamino)methyl)benzylcarbamoyloxy)butyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-phenoxypropan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-phenoxypropyl Methacrylate, 2-2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methylacrylate),3-Phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(phenylamino)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylamino)propyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloxy)-3-(phenylthio)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylthio)propyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(benzyloxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(benzyloxy)propyl Methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxomethylene)bis(oxy)bis, (3-(2-phenylacetoxy)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(2-phenylacetoxy)propan-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(2-phenylacetoxy)propyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2. 2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2. 2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1- diyl) diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)ethyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2, 2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxomethylene)bis(oxy)bis(ethane-2,1-diyl)diacrylate, 2-((2-(3-(2-(((2-(acryloyloxy)ethoxy)carbonyl)(methyl)amino)propan-2-yl)phenyl)propan-2-yl)(methyl)carbamoyloxy)ethyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)propyl methacrylate, 2-(2-(3-(2-((1-(acryloyloxy)propan-2-yloxy)carbonylamino)propan-2-ylcarbamoyloxy)ethyl Methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(4,1-phenylene)bis(2-methylacrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(4,1-phenylene)diacrylate, 4-(2-(3-(2-((4-(acryloyloxy)phenoxy)carbonylamino)propan-2-yl)phenyl )propan-2-ylcarbamoyloxy)phenyl methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)bis(2-methacrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(butane-4,1-diyl)diacrylate, 4-(2-(3-(2-((4-acryloyloxy)butoxy) carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)butyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-phenoxypropan-2-yloxy) carbonylamino) propan-2-yl) phenyl) propan-2-ylcarbamoyloxy)-3-phenoxypropyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylamino)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(phenylamino)propyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylthio)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(phenylthio)propyl Methacrylate, 2-2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(3-(benzyloxy)propane-2,1-diyl)bis(2-methylacrylate), 2-2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(3-(benzyloxy)propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(benzyloxy)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(benzyloxy)propyl Methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene )bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxomethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(2-phenylacetoxy)propan-2-yloxy)carbonylamino)propan-2-yl)phenyl)propan-2-ylcarbamoyloxy)-3-(2-phenylacetoxy)propyl methacrylate, etc.

[0054] The polymerization initiator contained in the medical and dental hardenable composition of the present invention can be selected from polymerization initiators used in the industrial field, and among them, polymerization initiators used for dental applications are preferably used. In particular, photopolymerization and chemical polymerization initiators are used alone or in appropriate combination of two or more. Specifically, photopolymerization initiators among the polymerization initiators contained in the medical and dental hardenable composition of the present invention include (bis)acylphosphine oxides, water-soluble acylphosphine oxides, thioxanthones or quaternary ammonium salts of thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, and α-aminoketone compounds. The ratio of these to the radical polymerizable monomer is preferably 0.5 wt% to 5 wt%. At a concentration lower than 0.5 wt%, the amount of unpolymerized radical polymerizable monomer increases, resulting in a decrease in mechanical strength. At a concentration higher than 5 wt%, the degree of polymerization decreases, resulting in a decrease in mechanical strength.

[0055] Specific examples of acylphosphine oxides used as photopolymerization initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoyldi-(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and (2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.

[0056] Specific examples of thioxanthones or quaternary ammonium salts of thioxanthones used as photopolymerization initiators include thioxanthones, 2-chlorothioxanthen-9-one, 2-hydroxy-3-(9-oxy-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(1-methyl-9-oxy-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N ,N,N-trimethyl-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, and the like.

[0057] Specific examples of α-diketones used as photopolymerization initiators include diacetyl, dibenzyl, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzyl, and acenaphthenequinone.

[0058] Specific examples of coumarin compounds used as photopolymerization initiators include 3,3'-carbonylbis(7-diethylamino)coumarin, 3-(4-methoxybenzoyl)coumarin, 3-chenoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, yl)coumarin, 3-benzoyl-8-methoxycoumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromocoumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 7-meth 3-(4-nitrobenzoyl)coumarin, 3-(4-nitrobenzoyl)coumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzyl)coumarin, 3-(4-phenyl-1,2-diphenylamino)-1,2-diphenyl-2,3-diphenyl ...3'-Carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazoyl)-7-(diethylamino)coumarin, 3-(2-benzothiazoyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazoyl)-7-(diethylamino)coumarin, 3-(2-benzothiazoyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,3'-carbonyl-7-diethylaminocoumarin Examples of compounds include phosphorus-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-1,1,7,7-tetramethyl1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazoyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.

[0059] Among the coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.

[0060] Specific examples of anthraquinones used as photopolymerization initiators include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.

[0061] Specific examples of benzoin alkyl ethers used as photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0062] Specific examples of α-aminoketones used as photopolymerization initiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one.

[0063] Among the photopolymerization initiators, it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides and their salts, α-diketones, and coumarin compounds, which provides a composition that is excellent in photocurability in the visible and near-ultraviolet regions and exhibits sufficient photocurability when using any of the light sources, such as a halogen lamp, a light-emitting diode (LED), and a xenon lamp.

[0064] Among the polymerization initiators contained in the medical and dental hardenable composition of the present invention, organic peroxides are preferably used as the chemical polymerization initiator. The organic peroxides used as the above-mentioned chemical polymerization initiator are not particularly limited, and known ones can be used. Representative organic peroxides include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates.

[0065] Specific examples of the ketone peroxide used as the chemical polymerization initiator include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.

[0066] Specific examples of hydroperoxides used as chemical polymerization initiators include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.

[0067] Specific examples of diacyl peroxides used as chemical polymerization initiators include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.

[0068] Specific examples of dialkyl peroxides used as chemical polymerization initiators include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.

[0069] Specific examples of peroxyketals used as chemical polymerization initiators include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, and 4,4-bis(t-butylperoxy)valeric acid-n-butyl ester.

[0070] Specific examples of peroxy esters used as chemical polymerization initiators include α-cumyl peroxy neodecanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxy isophthalate, di-t-butyl peroxy hexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxy acetate, t-butyl peroxy benzoate, and t-butyl peroxy maleric acid.

[0071] Specific examples of peroxydicarbonates used as chemical polymerization initiators include di-3-methoxyperoxydicarbonate, di-2-ethylhexylperoxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, diisopropylperoxydicarbonate, di-n-propylperoxydicarbonate, di-2-ethoxyethylperoxydicarbonate, and diallylperoxydicarbonate.

[0072] Among the organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is particularly preferably used.

[0073] Specific examples of the polymerization accelerator include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, and thiol compounds.

[0074] The amines used as polymerization accelerators are divided into aliphatic amines and aromatic amines.Specific examples of aliphatic amines include n-butylamine, n-hexylamine, n-octylamine, diisopropylamine, dibutylamine, N-methyldiethanolamine, N-methylethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, tributylamine, etc.Among these, from the viewpoint of the curability and storage stability of the composition, tertiary aliphatic amines are preferred, and among them, N-methyldiethanolamine and triethanolamine are more preferably used.

[0075] Specific examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-di(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-dimethyl-m-toluidine. dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-N,N-dimethylaminobenzoic acid ethyl ester, 4-N,N-dimethylaminobenzoic acid methyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, 4-N,N-dimethylaminobenzoic acid-2-(methacryloyloxy)ethyl ester, 4-N,N-dimethylaminobenzophenone, 4-dimethylaminobenzoic acid butyl, and the like. Among these, from the viewpoint of imparting excellent curing properties to the composition, N,N-di(2-hydroxyethyl)-p-toluidine, 4-N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, and 4-N,N-dimethylaminobenzophenone can be mentioned.

[0076] Specific examples of sulfinic acids and salts thereof used as the polymerization accelerator include p-toluenesulfinic acid, sodium p-toluenesulfinate, potassium p-toluenesulfinate, lithium p-toluenesulfinate, calcium p-toluenesulfinate, benzenesulfinic acid, sodium benzenesulfinate, potassium benzenesulfinate, lithium benzenesulfinate, calcium benzenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinate, potassium 2,4,6-trimethylbenzenesulfinate, lithium 2,4,6-trimethylbenzenesulfinate, calcium 2,4,6-trimethylbenzenesulfinate, 2,4,6-triethylbenzenesulfinate, and the like. Examples of the sulfinic acid include benzenesulfinic acid, sodium 2,4,6-triethylbenzenesulfinate, potassium 2,4,6-triethylbenzenesulfinate, lithium 2,4,6-triethylbenzenesulfinate, calcium 2,4,6-triethylbenzenesulfinate, 2,4,6-triisopropylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinate, potassium 2,4,6-triisopropylbenzenesulfinate, lithium 2,4,6-triisopropylbenzenesulfinate, and calcium 2,4,6-triisopropylbenzenesulfinate. Of these, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2,4,6-triisopropylbenzenesulfinate are particularly preferred.

[0077] Specific examples of the borate compound used as the polymerization accelerator include borate compounds having one aryl group in one molecule, such as trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(3,5-bistrifluoromethyl)phenyl boron, trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl] boron, trialkyl(p-nitrophenyl) boron, trialkyl(m-nitrophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(m-butylphenyl) boron, and trialkyl(p-nitrophenyl) boron. Examples of suitable alkyl groups include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of trialkyl(p-butyloxyphenyl)boron, trialkyl(m-butyloxyphenyl)boron, trialkyl(p-octyloxyphenyl)boron, and trialkyl(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0078] Specific examples of borate compounds having two aryl groups in one molecule include dialkyldiphenylboron, dialkyldi(p-chlorophenyl)boron, dialkyldi(p-fluorophenyl)boron, dialkyldi(3,5-bistrifluoromethyl)phenylboron, dialkyldi[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, dialkyldi(p-nitrophenyl)boron, dialkyldi(m-nitrophenyl)boron, dialkyldi(p-butylphenyl)boron, dialkyldi(m-butylphenyl)boron, and dialkyldi(p-butyloxophenyl)boron. Examples of such an alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of dialkyldi(m-butyloxyphenyl)boron, dialkyldi(p-octyloxyphenyl)boron, and dialkyldi(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0079] Further, specific examples of borate compounds having three aryl groups in one molecule include monoalkyltriphenylboron, monoalkyltri(p-chlorophenyl)boron, monoalkyltri(p-fluorophenyl)boron, monoalkyltri(3,5-bistrifluoromethyl)phenylboron, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, monoalkyltri(p-nitrophenyl)boron, monoalkyltri(m-nitrophenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(m-butylphenyl)boron, monoalkyltri(p ...butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(p-butylphenyl)boron Examples of the alkyl group include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of alkyltri(p-butyloxyphenyl)boron, monoalkyltri(m-butyloxyphenyl)boron, monoalkyltri(p-octyloxyphenyl)boron, and monoalkyltri(m-octyloxyphenyl)boron (wherein the alkyl group is one selected from an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).

[0080] Further specific examples of borate compounds having four aryl groups in one molecule include tetraphenylboron, tetrakis(p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis(3,5-bistrifluoromethyl)phenylboron, tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, tetrakis(p-nitrophenyl)boron, tetrakis(m-nitrophenyl)boron, tetrakis(p-butylphenyl)boron, tetrakis(m-butylphenyl)boron, tetrakis(p-butyloxyphenyl)boron, tetrakis(m-butyloxyphenyl)boron, tetrakis(p-octyloxyphenyl)boron, Examples of the salt include sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of (m-octyloxyphenyl)triphenylboron, (p-fluorophenyl)triphenylboron, (3,5-bistrifluoromethyl)phenyltriphenylboron, (p-nitrophenyl)triphenylboron, (m-butyloxyphenyl)triphenylboron, (p-butyloxyphenyl)triphenylboron, (m-octyloxyphenyl)triphenylboron, and (p-octyloxyphenyl)triphenylboron.

[0081] Among these aryl borate compounds, it is more preferable to use a borate compound having 3 or 4 aryl groups in one molecule from the viewpoint of storage stability. In addition, these aryl borate compounds can be used alone or in combination of two or more kinds.

[0082] Specific examples of barbituric acid derivatives used as polymerization accelerators include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, Examples of barbituric acids include 1-cyclohexyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and thiobarbituric acids, as well as salts thereof (particularly preferred are those of alkali metals or alkaline earth metals). Examples of the salts of these barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate, and sodium 1-cyclohexyl-5-ethylbarbiturate.

[0083] Specific examples of particularly suitable barbituric acid derivatives include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and sodium salts of these barbituric acids.

[0084] Specific examples of triazine compounds used as the polymerization accelerator include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methylthiophene)-4,6-bis(trichloromethyl)-s-triazine. 2-(p-phenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl) -4,6-bis(trichloromethyl)-s-triazine, 2-styryl-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, chloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,Examples of the 6-bis(trichloromethyl)-s-triazine include 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine and 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.

[0085] Among the above-listed triazine compounds, 2,4,6-tris(trichloromethyl)-s-triazine is particularly preferred in terms of polymerization activity, and 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine are particularly preferred in terms of storage stability. The above-listed triazine compounds may be used alone or in combination of two or more. Specific examples of copper compounds used as polymerization accelerators include copper acetylacetonate, copper acetate, copper oleate, copper chloride, and copper bromide.

[0086] Specific examples of tin compounds used as polymerization accelerators include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. Particularly preferred tin compounds are di-n-octyltin dilaurate and di-n-butyltin dilaurate.

[0087] The vanadium compound used as the polymerization accelerator is preferably a tetravalent and / or pentavalent vanadium compound. Specific examples of the tetravalent and / or pentavalent vanadium compound include divanadium(IV) tetroxide, vanadium oxide acetylacetonate(IV), vanadyl oxalate(IV), vanadyl sulfate(IV), oxo-bis(1-phenyl-1,3-butanedionato)vanadium(IV), bis(maltolato)oxo-vanadium(IV), vanadium pentoxide(V), sodium metavanadate(V), and ammonium metavanadate(V).

[0088] Specific examples of halogen compounds used as polymerization accelerators include dilauryl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, benzyl trimethyl ammonium chloride, tetramethyl ammonium chloride, benzyl dimethyl cetyl ammonium chloride, and dilauryl dimethyl ammonium bromide.

[0089] Specific examples of aldehydes used as polymerization accelerators include terephthalaldehyde and benzaldehyde derivatives. Examples of benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methyloxybenzaldehyde, p-ethyloxybenzaldehyde, and pn-octyloxybenzaldehyde. Among these, pn-octyloxybenzaldehyde is preferably used from the viewpoint of curability.

[0090] Specific examples of the thiol compound used as the polymerization accelerator include 3-mercaptopropyltrimethoxysilane, 2-mercaptobenzoxazole, decanethiol, and thiobenzoic acid. EXAMPLES

[0091] The synthesis of functional fine particles in which radically polymerizable groups are introduced via urethane bonds to hydroxyl groups on the surface of an inorganic filler, and the preparation method and physical properties of a medical and dental hardenable composition containing the functional fine particles will be described in detail below, but the present invention is not limited to these descriptions in any way.

[0092] Functional fine particle synthesis examples 1-5 According to the example formulation table in Table 1, the functional fine particles contained in the present invention were synthesized. OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Tatsumori Co., Ltd.) were used as inorganic fillers. The specific method is described below. The amount of each compound listed in the example formulation table in Table 1 was dissolved in 300 mL of dehydrated toluene, and added to a 500 mL eggplant flask containing 15.0 g of OX-50 and 40.0 g of Fuselex. Then, an electromagnetic stirrer was added and the mixture was stirred for 10 minutes, and further dispersed for 5 minutes using a 28 KHz-150 W ultrasonic disperser. After dispersion, the flask was immersed in an oil bath and refluxed for 5 hours. After refluxing, the internal temperature was returned to room temperature, and the mixture was transferred to a centrifuge tube and separated using a centrifuge. The supernatant toluene and the residue after heat treatment were removed by decantation to obtain a wet cake of functional fine particles. The wet cake was further heated to 40°C and the toluene was completely removed using a vacuum pump. The obtained functional fine particle block was dried at 110° C. for 12 hours and passed through a 200 mesh sieve to obtain a powder of functional fine particles.

[0093] Comparative Example: Microparticle Synthesis Examples 1 to 5 Surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Tatsumori Co., Ltd.) was performed using a commercially available polymerizable silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.) shown in Table 2. The specific surface modification method is described below. That is, the type and amount of silane coupling agent shown in Table 2 was dissolved in 300 g of ethanol, and added to a 500 mL eggplant flask containing 15.0 g of OX-50 and 40.0 g of Fuselex. Then, an electromagnetic stirrer was added and the mixture was stirred for 10 minutes, and further dispersed for 5 minutes using a 28 KHz-150 W ultrasonic disperser. After dispersion was completed, 1.8 g of distilled water and 1.2 g of a 1 wt% phosphoric acid aqueous solution were added under stirring, and the flask was immersed in a boiling water bath and refluxed for 5 hours. After refluxing was completed, the internal temperature was returned to room temperature, and the mixture was transferred to a centrifuge tube and separated using a centrifuge. The supernatant ethanol, the desorbed alcohol and water were removed by decantation to obtain a wet cake of the comparative example fine particles. The wet cake was further completely removed of ethanol and the like using a vacuum pump. The obtained comparative example fine particle block was dried at 110° C. for 12 hours and passed through a 200 mesh sieve to obtain a powder of comparative example fine particles.

[0094] Preparation of fluoroaluminosilicate powder (GI powder) A mixture of 240g SiO2, 204g Al2O3, 186g CaO, and 52g CaF2 was melted in an alumina crucible using an electric Erema furnace, and then quenched with water to obtain a colorless and transparent glass lump. This glass lump was crushed in a vibration mill using alumina media and passed through a sieve with 42μm openings to obtain fluoroaluminosilicate glass powder (GI powder).

[0095] Examples 1 to 5 A liquid formulation of a medical and dental curable composition was prepared with the composition shown in Table 3. A powder formulation of a medical and dental curable composition was prepared with the composition shown in Table 5.

[0096] Comparative Examples 1 to 5 A liquid formulation of a medical and dental curable composition was prepared with the composition shown in Table 4. A powder formulation of a medical and dental curable composition for comparison was prepared with the composition shown in Table 5.

[0097] Physical Property Testing The cement properties were evaluated according to ISO9917: Water-based cement standard (powder: 2.00g, liquid: 1.00g). Tables 6 and 7 show the physical property test results. The limit powder-liquid amount (g) means the amount of powder-liquid (amount of powder (g) per 1.0g of liquid) at which the coating degree measured 2 minutes after the start of mixing the powder-liquid (mixing time 60 seconds) exceeds 25 μm, and the greater the amount, the lower the initial viscosity of the mixture. In other words, it means that the viscosity of the mixture is low for some reason, and the operation of the dental hygienist or other practitioner is easy and the operability is excellent. From these test results, the medical and dental hardenable composition containing the functional fine particles of the present invention has a high compressive strength compared to the comparative examples, and the limit powder-liquid amount showed a very high value. In addition, since the initial viscosity of the powder-liquid mixture is low, there is sufficient fluidity, and the water-soluble monomer that is eluted due to this is suppressed. In other words, it is considered that sufficient fluidity promotes reliable polymerization of the water-soluble monomer. The medical and dental hardenable composition containing the functional fine particles produced by the present invention has clearly higher strength properties than medical and dental hardenable compositions using commonly used silane coupling agents (KBM-503, KBE-503). This is presumably because the surface treatment using a common silane coupling agent has a limit to the heating temperature, making complete dehydration and condensation difficult. In other words, it was difficult to completely eliminate the fragile xerogel layer. This xerogel layer is so-called silica gel, and it is thought that the viscosity increases when the powder and liquid are mixed because it has the property of absorbing liquids such as monomers. In response to these problems, the medical and dental hardenable composition containing the functional fine particles according to the present invention has radical polymerizable groups introduced from the inorganic filler surface via urethane bonds, which are covalent bonds, so that it is possible to obtain a very dense surface treatment layer without any fragile xerogel layer. In other words, it is possible to provide a medical and dental hardenable composition with high mechanical strength and operability that could not be achieved by conventional techniques.

[0098] [Table 1]

[0099]

Table 2

[0100]

Table 3

[0101]

Table 4

[0102]

Table 5

[0103]

Table 6

[0104]

Table 7

[0105] Compressive strength test in humid environment In Examples 1 to 5, the medical and dental hardenable compositions of the present invention were produced in an environment where the relative humidity of the laboratory was controlled at 50±5. In Examples 6 to 8, the medical and dental hardenable compositions of the present invention were produced in an environment where the relative humidity of the laboratory was controlled at 65±5%, 80±5%, and 95±5%, respectively. However, since the monomer for modifying the inorganic fine particles used in the present invention is an organic compound that has a radical polymerizable group at one end and generates an isocyanate group by heating, it is not affected by the relative humidity, and no statistically significant difference was detected in the physical property test results of Examples 6 to 8 compared to Example 1. In contrast, all of Comparative Examples 6 to 8 use a monomer (MOI) with an exposed isocyanate group. For this reason, it was concluded that the compressive strength results of the physical property test of the medical and dental hardenable compositions obtained tend to decrease as the relative humidity increases to 65±5%, 80±5%, and 95±5% when producing the medical and dental hardenable compositions. Furthermore, when the test results were subjected to an analysis of variance, it was found that there was a statistically significant difference between relative humidity and compressive strength.

[0106] [Table 8]

[0107] [Table 9]

[0108] [Table 10]

[0109] [Table 11]

[0110] Determination of silanol groups with trimethylchlorosilane The silanol groups react quantitatively and easily with trimethylchlorosilane due to their active hydrogen. In other words, it is possible to quantitatively determine the amount of silanol groups on the surface of inorganic fillers by adding a trimethylchlorosilane solution with a known concentration to a precisely weighed suspension of inorganic fine particles and quantifying the amount of remaining trimethylchlorosilane. The reaction proceeds smoothly if pyridine or other substances are added to remove the hydrogen chloride that is released and then removed from the system. The conceptual diagrams are shown below. Although not shown in the diagram, the hydrogen chloride that is produced precipitates out of the system as a pyridine salt.

[0111] [ka]

[0112] When the isocyanate group is deactivated by humidity and becomes a primary amine via carbamic acid, the silanol group forms a complex with the primary amine as shown in the figure below, and the number of active silanol groups is actually reduced. Therefore, the number of radically polymerizable groups finally introduced to the inorganic filler surface is limited. This is why the humidity in the comparative example leads to a decrease in the physical properties such as compressive strength of the final medical and dental hardenable composition. In addition, the radically polymerizable group (R in the figure) that forms a complex with the primary amine is a weaker bond than the urethane bond due to the σ bond, so it cannot contribute to improving the compressive strength.

[0113] [ka]

[0114] After leaving the inorganic filler for 10 minutes under each relative humidity in the table below, excess 2-isocyanatoethyl methacrylate was reacted in the presence of dibutyltin dilaurate and dehydrated toluene. Then, the bond between the primary amine and the inorganic filler complex was released by irradiating ultrasonic waves for 10 minutes with a 28KHz-150W ultrasonic disperser. After ultrasonic treatment, separation and decantation were repeated with a centrifuge to remove unreacted 2-isocyanatoethyl methacrylate. Then, excess chlorotrimethylsilane was reacted in the presence of dehydrated toluene and pyridine. After the reaction, the amount of unreacted chlorotrimethylsilane was quantified using a gas chromatograph equipped with a BID detector to quantify the amount of silanol groups complexed with the primary amine.

[0115] The table below shows the quantitative results of the silanol groups. Experiments 1 to 4 show the results using 2-isocyanatoethyl methacrylate, and Experiments 5 and 6 show the results using (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate. As can be seen from the table, as the relative humidity increases, 2-isocyanatoethyl methacrylate becomes 2-aminoethyl acrylate via carbamic acid, and the primary amine forms a complex with the silanol group, inhibiting the reaction of 2-isocyanatoethyl methacrylate with the silanol group. Thus, the medical and dental hardening composition using the inorganic filler prepared using (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate or 2-(3,5-dimethyl-1H-pyrazole-1-carboxamido)ethyl methacrylate, which is a compound that generates an isocyanate group by heating, showed higher physical properties than the medical and dental hardening composition using the inorganic filler prepared using the silanol group-reactive monomer with an exposed isocyanate group such as 2-isocyanatoethyl methacrylate.

[0116] [Table 12] [Industrial Applicability]

[0117] In general, (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate are used in medical and dental hardening compositions. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bonds are cleaved to single bonds, forming a polymer and hardening. In addition to vinyl monomers, inorganic fillers are added to medical and dental hardening compositions for the purpose of improving mechanical strength. In general, the surface of these inorganic fillers is treated with a silane coupling agent having a polymerizable group to improve wettability and mechanical strength. However, since these silane coupling agents have a carbon skeleton, there is a limit to the drying temperature, and the dehydration condensation of the generated silanol groups could not be completed. In other words, since they have a fragile xerogel layer, the current situation is that the expected mechanical strength cannot be obtained. The functional fine particles contained in the medical and dental hardenable composition of the present invention have radical polymerizable groups introduced from the inorganic filler surface via urethane bonds, which are covalent bonds, so that it is possible to obtain a very dense surface treatment layer without any fragile xerogel layer. As is clear from the above results, it is possible to provide medical and dental materials with high mechanical strength and durability that could not be achieved by conventional techniques. In this way, the present invention overcomes all the problems of conventional medical and dental hardenable compositions, and it can be said that the present invention has great potential for industrial use.

Claims

1. More than 90% of the silanol groups on the surface of the inorganic filler A functional fine particle having a radical polymerizable group introduced therein via a urethane bond.

2. The functional fine particles according to claim 1, characterized in that the inorganic filler serving as a base material for the functional fine particles according to claim 1 is at least one of silicon dioxide, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, and strontium calcium fluoroaluminosilicate glass.

3. A medical and dental hardenable composition comprising the functional fine particles according to claim 1.

4. A medical and dental hardenable composition comprising the functional fine particles according to claim 1, a radical polymerizable monomer, and a polymerization initiator.

5. 2. The medical and dental hardenable composition according to claim 1, comprising polyacrylic acid, a water-soluble radical polymerizable monomer, an acid-reactive inorganic powder, a polymerization initiator, an organic acid, and water.

6. The medical and dental hardenable composition according to claim 4 or 5, wherein the polymerization initiator is a carbonyl-based photopolymerization initiator and a reducing agent thereof.

7. The medical and dental hardenable composition according to claim 4 or 5, wherein the polymerization initiator is a redox polymerization initiator.

8. The medical and dental hardenable composition according to claim 5, wherein the water-soluble radically polymerizable monomer has an amide group or a urethane group.

9. 6. The medical and dental hardenable composition according to claim 5, wherein the content of the polyacrylic acid is 1 to 70% by weight, the content of the water-soluble radical polymerizable monomer is 1 to 50% by weight, the content of the acid-reactive inorganic powder is 0.1 to 90% by weight, the content of the polymerization initiator is 0.001 to 10% by weight, and the content of the organic acid is 0.01 to 25% by weight.

10. 6. The medical and dental hardenable composition according to claim 5, wherein the number of repeating acrylic acid monomers in the polyacrylic acid is within the range of 10 to 1,000.

11. 6. The medical and dental hardenable composition according to claim 5, wherein the acid-reactive inorganic powder is fluoroaluminosilicate glass.

12. 6. The medical and dental hardenable composition according to claim 5, wherein the organic acid is at least one selected from the group consisting of hydroxycarboxylic acids such as tartaric acid, malic acid, citric acid, maleic acid, itaconic acid and aconitic acid.

13. The water-soluble radical polymerizable monomer is methacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, N-isopropylacrylamide, bis(acrylamido)acetic acid, N-vinylpyrrolidone, N-vinyloxazolindone, N-vinylsuccinimide, N-vinylformamide, N-vinyl-N-methylformamide, N-vinylacetamide, N-vinyl-N-methylacetamide, N-methylolacrylamide, N-methylolmethacrylamide, methylenebisacrylamide, methylenebismethacrylamide, N-N'-(1,2-dihydroxy)ethylenebisacrylamide, 1,3,5-triacryloyl, hexahydro, s-triazine, hydroxyalkyl acrylate, hydroxyalkyl methacrylate, maleic anhydride, maleic acid, fumaric acid, itaconic acid, crotonic acid, cinnamic acid, vinylsulfonic acid, vinylsulfonic acid sodium 6. The medical and dental hardenable composition according to claim 5, characterized in that the at least one selected from the group consisting of sodium, sodium allylsulfonate, sodium methallylsulfonate, sodium styrenesulfonate, 2-sulfoethyl methacrylic acid, 2-sulfoethyl sodium methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, phosphorus-containing (meth)acrylic acid esters, phosphorus-containing acrylamide derivatives, aminoalkyl acrylates, aminoalkyl methacrylate esters, dimethylaminopropyl (meth)acrylamide, acrylamido-3-methylbutyldimethylamine and quaternary ammonium salts thereof, vinylpyridine, N-vinylimidazole, vinylbenzylammonium salts, diallylammonium salts, N-isopropylacrylamide, N-vinylimidazole, vinylbenzylammonium salts, diallylammonium salts, and acrylamide-N-glycolic acid.

Citation Information

Patent Citations

  • Dental reparative material

    JP1990134307A

  • Surface treatment of inorganic filler

    JP1991070778A

  • Silane coupling agent, and composite resin for dental application and primer for dental application each comprising the silane coupling agent

    JP2007238567A

  • New organosilicon compound, and composition comprising the same

    JP2010229054A